The Cerebral Cortex Overlying Periventricular Leukomalacia: Analysis of Pyramidal Neurons - Andiman, Sarah E. (Blackwell Publishing Ltd, 2010)
The role of the cerebral cortex in the cognitive deficits in preterm survivors is poorly understood. Periventricular leukomalacia (PVL), the key feature of encephalopathy of prematurity, is characterized by periventricular necrotic foci and diffuse gliosis in the surrounding cerebral white matter. Here, we tested the hypothesis that reductions in the density of layer I neurons and/or pyramidal neurons in layers III and/or V are associated with PVL, indicating cortical pathology potentially associated with cognitive deficits in long‐term survivors. In controls (23 gestational weeks to 18 postnatal months) (n = 15), a lack of significant differences in pyramidal density among incipient Brodmann areas suggested that cytoarchitectonic differences across functional areas are not fully mature in the fetal and infant periods. There was a marked reduction (38%) in the density of layer V neurons in all areas sampled in the PVL cases (n = 17) compared to controls (n = 12) adjusted for postconceptional age at or greater than 30 weeks, when the six‐layer cortex is visually distinct (P < 0.024). This may reflect a dying‐back loss of somata complicating transection of layer V axons projecting through the necrosis in the underlying white matter. This study underscores the potential role of secondary cortical injury in the encephalopathy of prematurity.